Behavioral Risk pada Investasi Logam Mulia : Analisis FOMO (Fear of Missing Out) di Kalangan Nasabah Pegadaian UPC Pasar Wadungasri - Aizzat Haqiqi; Mohammad Khusnu Milad (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the behavioral risk caused by the Fear of Missing Out (FOMO) phenomenon in precious metal investment decision making among Pegadaian UPC Pasar Wadungasri customers. This study uses a qualitative approach with a case study method, through in-depth interviews with 15 respondents aged 25–50 years. The results of the study indicate that most novice investors are driven to buy precious metals due to the influence of social media, viral trends, and social pressure, not based on rational considerations or mature financial planning. FOMO symptoms trigger impulsive, high-risk investment decisions with minimal information analysis. In contrast, more experienced customers show more careful, planned, and data-based investment behavior. These findings emphasize the importance of increasing financial literacy and the active role of financial institutions such as Pegadaian in educating the public to be able to build risk-aware, rational, and sustainable investment patterns amidst the rapid flow of digital information.